1996
DOI: 10.1096/fasebj.10.4.8647344
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by alternative promoters

Abstract: Promoters have been defined as modulatory DNA structures containing a complex array of cis-acting regulatory elements required for accurate and efficient initiation of transcription and for controlling expression of a gene. It is becoming increasingly evident that they also constitute prime target elements through which diversity and flexibility in the complex patterns of gene expression in multicellular organisms are created. The use of multiple promoters and transcription start sites is apparently a frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
224
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(231 citation statements)
references
References 20 publications
5
224
1
1
Order By: Relevance
“…The traditional view of a gene with its precisely defined and fixed TSS has been first challenged by the findings that many genes can be transcribed from multiple promoters (alternative promoters) producing functionally diverse transcripts [98,99]. Differential utilization of alternative promoters plays a critical role in regulating gene expression in a spatial, temporal or lineage-specific manner.…”
Section: Promoter Usage Dynamics Across Cell Types and Developmental mentioning
confidence: 99%
“…The traditional view of a gene with its precisely defined and fixed TSS has been first challenged by the findings that many genes can be transcribed from multiple promoters (alternative promoters) producing functionally diverse transcripts [98,99]. Differential utilization of alternative promoters plays a critical role in regulating gene expression in a spatial, temporal or lineage-specific manner.…”
Section: Promoter Usage Dynamics Across Cell Types and Developmental mentioning
confidence: 99%
“…The few polymorphisms that do exist in basal promoters appear to contribute little to variable gene expression among strains of D. melanogaster (Brown and Feder, 2005). Genes can also contain multiple, alternative promoters that are active under different cellular conditions (Ayoubi and Van De Ven, 1996). The contribution of alternative promoters to regulatory divergence remains unclear.…”
Section: Enhancers Control Patterns Of Gene Expressionmentioning
confidence: 99%
“…Like many other globin genes (24,31), the sequences of the TATA boxes of the N. coriiceps promoters deviate from the vertebrate canon, TATAAA (33). The use of alternative promoters and multiple transcription initiation sites to regulate gene expression in eukaryotes is now recognized to be a common phenomenon (37). For example, Hu et al (38) have shown that tissue-specific expression of prolactin receptors in the rat is controlled by three promoters, two of which contain noncanonical TATA elements.…”
Section: ␣-Globin Gene Remnants In Antarctic Icefishesmentioning
confidence: 99%